2018
DOI: 10.4995/redu.2018.10190
|View full text |Cite
|
Sign up to set email alerts
|

El trabajo de fin de grado: resultados desde una perspectiva de pares estudiantes/tutores

Abstract: <p>La investigación sobre el Trabajo de Fin de Grado (TFG) ha ido incorporando aspectos de la interacción tutor-a/alumno-a que se han demostrado cruciales en la explicación de los resultados de estos últimos. Merece particular atención el apoyo tutorial recibido durante la realización del trabajo -en naturaleza e intensidad- y su relación con los resultados obtenidos. El estudio de esta relación es el objetivo de este artículo que, a través del análisis de la información aportada por 178 pares alumno-a/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
(15 reference statements)
0
4
0
6
Order By: Relevance
“…Preceding studies tried to identify the generic and specific competences associated with development of the FYP, however lacking student's integrative understanding (Mateo et al 2012;Rullán et al 2010;Reyes-García & Díaz-Megolla, 2020;Expósito-Díaz et al, 2018;Ruiz-Lozano & Tirado-Valencia, 2016). Conversely, our results depicted an integrative understanding of student's perceptions, assessing not only if they consider, for instance, if decision-making is important, or learning capacity, but rather given a step further in understanding how they use different skills in combination when developing particular tasks -in this case, different activities, conceptual approaches and guidelines around the FYP development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preceding studies tried to identify the generic and specific competences associated with development of the FYP, however lacking student's integrative understanding (Mateo et al 2012;Rullán et al 2010;Reyes-García & Díaz-Megolla, 2020;Expósito-Díaz et al, 2018;Ruiz-Lozano & Tirado-Valencia, 2016). Conversely, our results depicted an integrative understanding of student's perceptions, assessing not only if they consider, for instance, if decision-making is important, or learning capacity, but rather given a step further in understanding how they use different skills in combination when developing particular tasks -in this case, different activities, conceptual approaches and guidelines around the FYP development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified that students perceived to have improved most of their generic skills when developing their FYP (Ruiz-Lozano & Tirado-Valencia 2016;Expósito-Díaz et al, 2018), and depicted shortages in skills related to innovation, creativity, ethical commitment or oral communication. These results coincide in part with our findings, as overall students' perceived improvements across different competencies and also entrepreneurial related skills were lower-valued by the three profiles identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hay autores que señalan que el rol ejercido por el tutor influye en las habilidades desarrolladas por el alumno en su TFG (Expósito et al, 2018;Del Río et al, 2018). Por ello, resulta imprescindible el desarrollo de un correcto proceso de supervisión del TFG.…”
Section: La Direccion De Trabajos Fin De Gradounclassified
“…A pesar de la importancia académica que tiene la realización del TFG, hay escasa evidencia empírica acerca del proceso de dirección de los TFG, centrándose más en el ámbito de la evaluación de estos (Ortiz-Repiso, García Zorita, Pacios, & Vianello, 2014;Starr-Glass & Ali, 2012;Webster, Pepper, & Jenkins, 2000) que en el proceso de gestión y dirección de aquellos (Derounian, 2011;Expósito et al, 2018;Rowley & Slack, 2004;Shadforth & Harvey, 2003). No obstante, un elemento esencial del éxito en la realización del TFG es la labor y el papel ejercido por el tutor, apoyando y guiando al alumno (Expósito Díaz et al, 2018). Conviene señalar además que la dirección de TFG puede ser una tarea intensiva en tiempo para el tutor, y donde el rol que ejerce el tutor puede variar en el tiempo, desarrollándose distintos roles complementarios (Rowley & Slack, 2004).…”
Section: Introductionunclassified